Pengaruh Sistem Informasi Akuntansi Penjualan Terhadap Efektivitas Pengendalian Piutang Pada Pt. Enseval Putera Megatrading, Tbk Cabang Sukabumi - Asep Awaludin (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2020)
This study aims to determine the effect of accounting information system sales of the effectiveness of the control receivables at PT. Enseval Putera Megatrading, Tbk branch of Sukabumi. By using quantitative descriptive method that describes the relationship between variables to analyze numerical data (numbers) using methods statistika through hypothesis testing. The authors determined that the accounting information system sales as the independent variable (free) and accounts receivable control as the dependent variable (linked). Of the 30 questionnaires distributed to respondents, and inserted into the data processing, data analysis using SPSS version 23. The statistical method used to test the hypothesis adalan simple linear regression analysis. Having analyzed showed that the accounting information system sales positive effect on accounts receivable control. The coefficient of determination shows the accounting information system sales is acceptable to the effectiveness of receivables by 48.4% and the rest influenced by other factors not examined at 51.6%